2016
DOI: 10.1186/s12978-016-0157-5
|View full text |Cite|
|
Sign up to set email alerts
|

Improving access to safe abortion in a rural primary care setting in India: experience of a service delivery intervention

Abstract: BackgroundAbortion services were legalized in India in 1972, however, the access to safe abortion services is restricted, especially in rural areas. In 2002, medical abortion using mifepristone- misoprostol was approved for termination of pregnancy, however, its use has been limited in primary care settings.MethodsThis paper describes a service delivery intervention for women attending with unwanted pregnancies over 14 years in four primary care clinics of Rajasthan, India. Prospective data was collected to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…in an urban slum of Delhi, which showed that 16% of participants had undergone one or more induced abortions. However, in an investigation conducted in Rajasthan, 20% of married women reported having had at least one induced abortion at least once.…”
Section: Discussionmentioning
confidence: 99%
“…in an urban slum of Delhi, which showed that 16% of participants had undergone one or more induced abortions. However, in an investigation conducted in Rajasthan, 20% of married women reported having had at least one induced abortion at least once.…”
Section: Discussionmentioning
confidence: 99%
“…About 70% of India’s population live in rural settings, but safe abortion services are rarely available at rural facilities 21. In the state of Rajasthan, for example, rural settings had an estimated 0.85 certified abortion facilities per 100 000 population, compared with 3.65 in urban settings 27…”
Section: Discussionmentioning
confidence: 99%
“…4 Even where trained providers exist, most do not give women a choice of options, whereas data from studies have shown that women overwhelmingly prefer medical abortion. 5 Furthermore, over-medicalised service delivery protocols are in use for medical abortion, which is approved for use only up to 9 gestational weeks in India. 6 Although a large proportion of abortions in India are provided outside a legal framework, not all will necessarily have been unsafe.…”
Section: A Need For Overhaul Of Policy On Contraception and Abortion mentioning
confidence: 99%